USF1 Transcriptionally Regulates UGT1A3 and Promotes Lung Adenocarcinoma Progression by Regulating Neurotrophin Signaling Pathway - Wang, Yu; Zhao, Yun-Xia; Zhang, Xiang-Wei; Jiang, Yuan-Zhu; Ma, Wei; Zhang, Lin; Dong, Wei (Frontiers in Molecular Biosciences, 2022)
Abstract Background: Lung cancer remains the leading cause of oncological death. There is an urgent need to discover new molecular targets and to develop new treatments. Our previous study showed that one of the UDP-glucuronosyltransferases (UGTs) family, UGT1A3, is an important prognostic factor for lung adenocarcinoma (LUAD), inhibiting UGT1A3 could significantly improve the efficacy of anti-tumor drugs. In this study, we aimed to explore the upstream transcriptional factor (USF1) of UGT1A3 and its way of playing a role in LUAD. Methods: The UGT1A3 promoter region was analyzed and dual-luciferase assay was involved to explore whether USF1 could bind to this region, and the possible regulation effects of USF1 to UGT1A3 was indicated by siRNA and recovery experiment. Then, the Cancer Genome Atlas database was used to analyze USF1 clinical features. The expression level of USF1 was detected by immunohistochemical assay and Western blotting. Cellular viability, proliferation, migration and invasion potential were also investigated. Meanwhile, the effect of USF1 in LUAD progression was detected in a mouse model. The downstream signaling pathway was analyzed by bioinformatic analysis and the expression of all related proteins was detected. Results: UGT1A3 was translationally regulated by USF1, which was highly expressed in all investigated samples including patients’ tissues, studied cells lines, and mouse models. The knockdown of USF1 inhibited cells viability, proliferation, migration and invasion, and reduced the tumor volume. Moreover, USF1 promoted the progress of LUAD by regulating the neurotrophin signaling pathway. Conclusion: As an important transcriptional regulator of UGT1A3, USF1 was highly expressed in LUAD and promoted LUAD progression by regulating the neurotrophin signaling pathway. These findings provide a new theoretical data that could serve as a good foundation for the treatment of LUAD.